The creative imagination of university students of the specialty of Psychology - Zambrano Bravo, Lynn Katherine (2019)
The purpose of this study is to determine the predominant dimension in the creative imagination of students of psychology, with creative imagination understood as the ability to invent new situations, products or solutions beyond reproducing them from previous knowledge. This research study design is substantive, descriptive and explanatory. The study sample is composed of 85 students between 16 and 18 years of the Faculty of Psychology of the César Vallejo University. An instrument called PIC-J (Test of creative imagination for young people) was used, construct validity was performed through construct analysis and reliability through the Cronbach Alpha. The testing of the hypotheses was made through the logistic regression and these results show that the predominant dimension is narrative creativity and the relevant indicators are fluency and originality, which are fundamental for the students.